Awareness and Perceptions of Health Promotion Strategies Among Caregivers to Reduce Child Mortality in Mount Fletcher, Eastern Cape, South Africa - Lulama Lathitha Faku; Mirable Nanjoh; Luviwe Lutotswana; Monwabisi Faleni; Mbuyiselo Douglas; Ziphelele Peter (F1000Research, 2026)
Background Child mortality remains a major public health challenge in low- and middle-income countries, with Sub-Saharan Africa carrying a disproportionate share of the global burden. In South Africa, rural and under-resourced areas such as Mount Fletcher in the Eastern Cape continue to record high rates of preventable under-five deaths. The effectiveness of national and provincial health promotion strategies depends heavily on local awareness, acceptance, and participation, yet little is known about how caregivers in rural communities such as Mount Fletcher understand and experience these interventions. Objective To explore the awareness and perceptions of health promotion strategies among caregivers to reduce child mortality in Mount Fletcher, and to identify the barriers and facilitators influencing their uptake. Methods A qualitative descriptive study was conducted among 20 mothers and primary caregivers of children under five years attending Taylor Bequest Clinic in Mount Fletcher, Elundini Local Municipality. Participants were selected through purposive sampling and took part in semi-structured, audio-recorded interviews conducted in isiXhosa or English. Data were transcribed verbatim and analysed thematically using ATLAS.ti (version 8), guided by the Health Belief Model. Results Participants demonstrated good awareness of core child-survival interventions, including immunisation, exclusive breastfeeding, nutrition, hygiene, and clinic attendance, and generally held positive attitudes toward health promotion services and healthcare workers. However, participants identified substantial barriers to the uptake of these strategies, including poverty, transport costs and distance to health facilities, long clinic waiting times and staff shortages, and the continued influence of traditional and cultural beliefs on health-seeking behaviour. Conclusion Caregivers in Mount Fletcher are broadly aware of, and hold favourable attitudes toward, child health promotion strategies, but structural, economic, and cultural barriers continue to limit their consistent use. Strengthening community health worker outreach, addressing health system constraints, and engaging traditional and community leaders alongside biomedical health education may help translate existing awareness into more consistent uptake of child mortality reduction interventions in similar rural South African settings.